Environmental hydraulics of brine discharges for large scale desalination plants in coastal waters : the occurrence of bifurcation - Huang, Dingyong. (2013)
In this study, Planar Laser Induced Florescence (PLIF) was used to image negatively buoyant jets at low Reynolds numbers. Some of the key features observed were the downward plume, pseudo secondary jet and peeling off effect. Three types of jet structures were also observed. Type 1 structures had a strong downward plume, Type 2 structures had a weaker downward plume and a pseudo secondary jet and Type 3 structures were typical horizontal turbulent dense jets. It was noted that the peeling off effect was evident for Type 1 and Type 2 structures and their mechanisms differed slightly from each other. Bifurcation was defined as the development of a separate stream that is completely independent of the primary jet in this study. Based on the analysis of instantaneous images of positively buoyant jets at low Reynolds numbers, no bifurcation was deemed to have occurred as the secondary jet that arose was pseudo and a thin sheet of fluid existed between the pseudo secondary jet and primary jet. Bifurcation was also found to be inapplicable to negatively buoyant jets at low Reynolds numbers due to the inexistence of any separate independent stream of fluid from the primary jet. The centerline concentration decays of negatively buoyant jets at low Reynolds numbers were analysed and the decay constants were found to be approximately 0.7 for most of the cases. In addition, it was found that although lower Reynolds number jets had higher decay constants, there was a limiting Reynolds number before the enhanced centreline decay became counter-efficient. Lastly, skewness was used to determine the point of transition where the downward plume became insignificant. With the exception of Test B6, the boundary tallied with the change in decay constants as the jet transited from a Type 1 (for Gr1/2=115) or Type 2 (for Gr1/2=200) into a Type 3 structure.